L’œuvre en devenir - Jean-Paul Fourmentraux (Communication)
In the digital age artistic work aims to conceive of interactive mechanisms as much as to produce forms of communication and exhibition where the public can be implicated into the process of the work. In this context, Internet sites, homepages, online workshops, mailing lists and discussion forums constitute renewed forms of sociability. On the one hand, the artist creates a space in which s/he both lives and enriches by accumulating data with the aim of creating a more or less « living » archive. On the other, s/he configures this space through servers, accesses and addresses as a universe to be experienced and lived from the inside, thus inviting the cyber visitor to temporarily inhabit the space. This article proposes a description of these relational modes between the artist and his/her audience in a context where the creation of the work of art appears to be indistinguishable from the act of reception of content which is hitherto characterized by its modularity and openness. Through the construction and distribution of this editorial content and the reading practices that make them actual, the article questions the mechanisms (frames, interfaces) and the concrete modalities of this digital sociability (contracts, rituals).